Research on the coupling of talent cultivation and reform practice of higher education in architecture - Zhiwu Zhou; Qiong Tian; Julián Alcalá; Víctor Yepes (Computers and Education Open, 2025)
With the sustainable development of the global construction industry and the rapid development of the intelligent building industry, colleges and universities worldwide are stepping up the training of comprehensive talents in intelligent application in the construction profession. Therefore, establishing a cross-regional and perfect construction talent training system has become a critical research and practice topic for university researchers. This study uses computational procedures to fit mathematical theories, coupled model analysis, and other innovative training framework systems. It also analyzes the problems and shortcomings in talent training from three aspects: the current status of industrialization of higher education construction at home and abroad. Combined with the current status of talent training in higher education and the different needs of various countries for architectural talents, a Chinese-style ''six-stage multi-module innovation optimization'' training framework and a ''construction talent training model'' are proposed to improve the innovation system. Through in-depth research, a talent training goal system and improvement strategy adapted to the development of China's construction industrialization have been established. The research results effectively compensate for the shortcomings of higher vocational education in this field. The framework of this study can serve as a beacon for deepening education in the construction profession in various countries around the world, guiding higher vocational education to move towards the training of high-tech and high-skilled talents.